Untranslatable Japanese business terminology: A qualitative study on culture-bound loanwords retained in global English communication - Reswari, Girindra Putri Ardana; Trahutami, Sriwahyu Istana (Japanese Research on Linguistics, Literature, and Culture, 2025)
Some culturally rooted Japanese business phrases do not have the precise equivalents in English business terminologies. It is prompting the translators, multinational corporations, and worldwide media to use the original Japanese lexical form. This study examines how Japanese business terms like omotenashi, ikigai, and senpai- kōhai, are used in English-language business discourse. Data were gathered from corporate records, international business media, and academic publications between 2019 and 2024. Grounded in Jakobson's (1995) in theory of cultural untranslatability and further informed by Appiah (1993) notion of thick translation and Skopos Theory (Vermeer, 1978) and by using a qualitative discourse-analytic approach supported by lexical content analysis, the study identified three main reasons for translation retention: (1) high cultural density and embedded socio-ethical values, (2) lack of conceptual equivalence in English, and (3) strategic branding that leverages " Japanese " for global market identity. The findings reveal that explanatory paraphrasing and loanword preservation regularly coexist, implying that English-language business communication employs hybrid semantic representation to accommodate Japanese concepts. The study comes to the conclusion that leadership practice, worldwide brand positioning, and intercultural business negotiations are all influenced by untranslatable business concepts.